A Community Engagement Approach To Enhancing Teachers’ Competence In Developing Sundanese Learning Materials For Primary Schools - Yudhie Suchyadi; Rini Sri Indriani; Resyi A Gani; Nita Karmila; Dilla Eka Aprilia; Haula Ramadhanie; Kamilah Nuraini; Muhamad Irsyad Azharul HaQ (UNIVERSITAS PAKUAN, 2026)
This community engagement program aims to enhance primary school teachers’ competence in developing Sundanese learning materials that are contextual, innovative, and aligned with the characteristics of elementary school students. The program was implemented at SD Negeri Kedung Badak 2, Bogor City, involving a group of elementary school teachers as the main partners. The activities were conducted through several stages, including needs assessment, training on instructional material development, workshops for designing Sundanese learning materials, and mentoring during classroom implementation. The program emphasized the integration of local wisdom and cultural values of Sundanese society into learning materials to support meaningful and culturally relevant learning. The results of the program indicate a significant improvement in teachers’ pedagogical competence, particularly in designing contextual learning materials such as modules, worksheets, and simple learning media. Teachers demonstrated increased ability to develop innovative instructional resources and apply them effectively in classroom practices. Furthermore, the implementation of the developed materials contributed to higher student engagement and motivation in learning Sundanese language and culture. This community engagement initiative highlights the importance of collaborative partnerships between universities and schools in strengthening teachers’ professional capacity and promoting the preservation of local culture through primary education.